Hyperthyroidism is not a significant risk of benign prostatic hyperplasia: A nationwide population-based study. Issue 39 (September 2018) - Man, Kee-Ming; Chen, Kuen-Bao; Chen, Huey-Yi; Chiang, Jen-Huai; Su, Yuan-Chih; Man, Samantha S.; Xie, Dong-Dong; Wang, Yi; Zhang, Zhi-Qiang; Bi, Liang-kuan; Zhang, Tao; Yu, De-Xin; et al.
Abstract : Abstract: Benign prostatic hyperplasia (BPH) is a common disorder in the aging male population. Despite evidence that thyroid status impacts the prostate, the objective of this study was to examine whether patients with hyperthyroidism were at a greater risk for BPH. This study is a retrospective nationwide population-based cohort study of the Chinese population. Data for this study were retrieved from the Taiwan National Health Insurance Research Database (NHIRD). Overall, 1032 male patients aged 40 years or older with hyperthyroidism diagnosed between 2000 and 2006 were included in the hyperthyroidism group, and 4128 matched controls without hyperthyroidism were included in the non-hyperthyroidism group. Both groups were monitored until the end of 2011. A Cox proportional hazards regression model was used to compute and compare the risk of BPH between study participants with and those without hyperthyroidism. Patients with hyperthyroidism exhibited a greater incidence of BPH (18.51% vs 15.53%) than did the controls. Furthermore, the hazard ratio (HR) of the hyperthyroidism group was 1.24 times that of the control group [95% confidence interval (95% CI 1.05–1.46)] signifying that there is a significant 24% increase in the risk of BPH with the presence of hyperthyroidism. This increased risk of BPH with hyperthyroidism, however, failed to remain significant (adjusted HR = 1.11, 95% CI = 0.94–1.3) after adjusting for covariates of age (adjusted HR = 2.72, 95% CI = 2.32–3.2), diabetes (adjusted HR = 1.4, 95% CI = 1.17–1.68), hypertension (adjusted HR = 1.74, 95% CI = 1.49–2.03), hyperlipidemia (adjusted HR = 1.25, 95% CI = 1.03–1.53), neurogenic bladder, cystitis (adjusted HR = 1.23, 95% CI = 0.58–2.59), urethral stricture (adjusted HR = 2.01, 95% CI = 0.28–14.47), urethritis (adjusted HR = 1.52, 95% CI = 0.72–3.21), and urinary tract infection (adjusted HR = 1.77, 95% CI = 1.31–2.39). After adjustment for comorbidities and covariates, hyperthyroidism was not found to be a significant risk factor of BPH in our male study subjects. Further research is warranted to validate our results and elucidate the association of the pathophysiology of these 2 diseases.